ChemInform Abstract: Simple Alcohols Promoted Direct C—H Arylation of Unactivated Arenes with Aryl Halides. Issue 29 (1st July 2013) - Liu, Wei; Tian, Fei; Wang, Xiaolei; Yu, Hao; Bi, Yanlan
Abstract It is assumed that simple alcohols serve to promote the radical formation.